Cellular Senescence and Regulated Cell Death of Tubular Epithelial Cells in Diabetic Kidney Disease - Shen, Shuang; Ji, Chuanyuan; Wei, Kaifeng (Frontiers in Endocrinology, 2022)
Cellular senescence is frequently evident at etiologic sites of chronic diseases and involves essentially irreversible arrest of cell proliferation, increased protein production, resistance to apoptosis, and altered metabolic activity. Regulated cell death plays a vital role in shaping fully functional organs during the developmental process, coordinating adaptive or non-adaptive responses, and coping with long-term harmful intracellular or extracellular homeostasis disturbances. In recent years, the concept of ‘diabetic tubulopathy’ has emerged. tubular epithelial cells are particularly susceptible to the derangements of diabetic state because of the virtue of the high energy requirements and reliance on aerobic metabolism render. Hyperglycemia, oxidative stress, persistent chronic inflammation, glucose toxicity, advanced glycation end-products (AGEs) accumulation, lipid metabolism disorders, and lipotoxicity contribute to the cellular senescence and different patterns of regulated cell death (apoptosis, autophagic cell death, necroptosis, pyroptosis, and ferroptosis) in tubular epithelial cells. We now explore the ‘tubulocentric’ view of diabetic kidney disease(DKD). And we summarize recent discoveries regarding the development and regulatory mechanisms of cellular senescence, apoptosis, autophagy, necroptosis, pyroptosis, and ferroptosis in the pathogenesis of DKD. These findings provide new perspectives on the mechanisms of DKD and are useful for designing novel therapeutic approaches for the treatment of DKD.